2011
DOI: 10.5860/crl-117rl
|View full text |Cite
|
Sign up to set email alerts
|

Helping International Students Succeed Academically through Research Process and Plagiarism Workshops

Abstract: Workshops on the research process and plagiarism were designed to meet the needs of international students at the University at Albany. The research process workshop covered formulating research questions, as well as locating and evaluating sources. The plagiarism workshop focused on acknowledging sources, quoting, paraphrasing, and summarizing materials, citation styles, and avoiding plagiarism. The effectiveness of the workshops was measured by administering pre-and post-tests and by interviewing students se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 10 publications
0
34
0
1
Order By: Relevance
“…The students who took part in the workshops also took pre-and post-tests. The results of these tests showed that the d ' k wl dg b pl gi i m h d imp v d f h vi g d d the workshops (Chen & Ullen, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The students who took part in the workshops also took pre-and post-tests. The results of these tests showed that the d ' k wl dg b pl gi i m h d imp v d f h vi g d d the workshops (Chen & Ullen, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most previous research concurs that international students face challenges in seeking and using information (Ishimura & Bartlett, 2014;Liu & Winn, 2009;Ramachandran, 2014;Sato & Hodge, 2009;Hensley & Love, 2011;Chen & Van Ullen, 2011), including language barriers, general cultural adjustments, research and writing skills, and familiarity with library systems (Hensley & Love, 2011;Ishimura & Bartlett, 2014).…”
Section: Literature Reviewmentioning
confidence: 89%
“…Testing was used in four of the studies, albeit by slightly different names such as skills testing, 35 multiple choice testing, 36 or pre-and post-testing. 37 Eighteen (26%) of the studies used mixed research methods including different combinations of the following: surveys, testing, writing analysis, 38 focus groups, 39 interviews, 40 website content analysis, 41 research portfolios, 42 key tracking, 43 and collection usage statistics. 44 Within the mixed method category, all 18 of the studies used surveys or interviews combined with other methods.…”
Section: Research Methods and Theoriesmentioning
confidence: 99%